2023
DOI: 10.1007/s13755-023-00231-0
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal learning of clinically accessible tests to aid diagnosis of neurodegenerative disorders: a scoping review

Abstract: With ageing populations around the world, there is a rapid rise in the number of people with Alzheimer’s disease (AD) and Parkinson’s disease (PD), the two most common types of neurodegenerative disorders. There is an urgent need to find new ways of aiding early diagnosis of these conditions. Multimodal learning of clinically accessible data is a relatively new approach that holds great potential to support early precise diagnosis. This scoping review follows the PRSIMA guidelines and we analysed 46 papers, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The use of computer vision methods to extract finger‐tapping features to predict cognitive performance is novel 3 , 5 , 16 and efficient 12 but similar methods are increasingly being used to quantify various movement disorders as they are objective and granular, unlike clinical rating scales, 44 and provide evaluation of movements in 3D space through simple smartphones or laptops. 14 , 15 , 45 Computer vision approaches facilitate wide reach and accessibility, including to those in rural and remote regions, as webcams are so ubiquitous in phones and computers around the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of computer vision methods to extract finger‐tapping features to predict cognitive performance is novel 3 , 5 , 16 and efficient 12 but similar methods are increasingly being used to quantify various movement disorders as they are objective and granular, unlike clinical rating scales, 44 and provide evaluation of movements in 3D space through simple smartphones or laptops. 14 , 15 , 45 Computer vision approaches facilitate wide reach and accessibility, including to those in rural and remote regions, as webcams are so ubiquitous in phones and computers around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) accounts for more than 70% of cases, and the pathology begins 10–20 years before any overt cognitive symptoms emerge 2 . Developing simple, low‐cost tests to detect this preclinical stage is a research priority for drug development and enriching cohorts for dementia prevention 3 . However, we currently lack cost‐effective population‐level tests to risk stratify asymptomatic community samples; cognitive test performance is highly correlated with intelligence and education, and some people are more resilient to cognitive decline, carrying a higher burden of pathology for longer before cognitive test performance starts to decline 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we plan to combine analysis of repetitive hand movements (finger-to-thumb tapping) with analysis of speech-like movements (through the DDK test) to provide a more sensitive and inclusive means for detecting AD pathology. This ‘multimodal’ approach will use digital video data for finger tapping analysis combined with audio data for DDK data and is expected to improve the accuracy of the test compared to using a single type of test; a scoping review of 46 studies and 11,750 participants found that, applying a multimodal approach improves the sensitivity and specificity of tests to detect AD and other neurodegenerative disorders [ 36 ]. In further support of this proposal, it is noteworthy that the hand and lips-tongue-palate areas in the cerebral cortex share a close topographical relationship, suggesting shared movement pathways [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, despite extensive research efforts, the early detection, effective treatment, and understanding of the molecular mechanisms underlying AD remain largely elusive. 4 , 5 Therefore, it is important to develop dependable diagnostic methods for the identification of AD biomarkers, particularly in the initial phases.…”
Section: Introductionmentioning
confidence: 99%